Positive distraction in daily activities as a predictor of good coping: A “day in the life” during the COVID-19 pandemic - Leslie-Miller, Calissa J.; Cole, Veronica T.; Waugh, Christian E. (Frontiers in Psychology, 2023)
Introduction The early part of the coronavirus pandemic (COVID-19) was a chronic stressor that led to decreased life satisfaction, increased psychopathology, and decreased social interaction, making it important to study coping strategies that stimulate increases in emotional well-being. Previous research has demonstrated that disengagement coping may be beneficial in scenarios where engagement coping is too difficult or not possible. We hypothesized that disengagement coping would be related to good emotional well-being (high positive emotions and/or perceived control, lower negative emotions and/or stress), with distraction (taking a break from a stressor) related to better emotional well-being than is avoidance (avoiding thoughts and feelings associated with a stressor). Methods Using a daily reconstruction method that represents a “day in the life” of people in the United States during the early stages of the COVID-19 pandemic, we assessed people’s (N = 329) activities, their intention to distract from or avoid the stressor during these activities, emotions, and thoughts about and motivation to deal with COVID. Results Between-subjects’ analyses revealed that habitual distraction did not predict any outcomes, while habitual avoidance related to poorer emotional well-being. Within-subject analyses, however, demonstrated that engaging in distraction (and to a smaller extent, avoidance) was associated with better concurrent emotional well-being and less thinking about COVID. Furthermore, the intent to distract/avoid was more reliable in predicting emotional outcomes than was the activity type. Conclusion These findings suggest that disengagement from stress can be an adaptive coping behavior during global pandemics and possibly other chronic stressors with similar attributes.